Frequency-Dependent Medial Septal Nucleus Deep Brain Stimulation Modulates Hippocampal Oscillatory Activity and Improves Spatial Working Memory in an MK-801 Model of Schizophrenia. (16th November 2020) - Zepeda, Nancy; Gifford, Raymond; Choi, Wooseong; Sheth, Megha; Medvidovic, Sasha; Bergosh, Matthew; Lu, Gengxi; Folz, Caroline; Lee, Darrin J
Abstract: INTRODUCTION: Schizophrenia is a debilitating psychiatric disease characterized by positive, negative and cognitive symptoms. Pharmacological models targeting glutamate N-methyl-D-aspartate (NMDA) receptor hypofunction (such as MK-801) mimic these symptoms and disrupted neural oscillatory activity, such as decreased hippocampal theta (5-12 Hz) activity. METHODS: 47 male Sprague-Dawley rats underwent implantation of hippocampal, prefrontal cortex (PFC) and thalamic recording electrodes and an MSN stimulating electrode. Rodents underwent sham (n = 13) or MK-801 (n = 31) intraperitoneal injections 30 minutes prior to baseline recordings and each Barnes maze task. During the behavioral task, MK-801 rats received no stimulation, theta (7.7 Hz) stimulation or gamma (100 Hz) stimulation. Latency to finding the escape hole was recorded. RESULTS: MK-801 rats had reduced hippocampal theta power ( P < .05) compared to sham animals, but were not different in PFC ( P = .88) or thalamic theta power ( P = .05). On the Barnes maze, MK-801 animals had longer latencies relative to sham animals on post-surgery days 12–14 ( P < .05). MK-801 animals without stimulation had a longer latency than sham animals (145.0±26.0 vs. 55.3±10.9 seconds, P < .001). MK-801 animals with theta stimulation had shorter latencies than MK-801 animals without stimulation (48.6±14.8 seconds, P < .001); however, MK-801 animals with gamma stimulation were no different than MK-801 animals without stimulation (182.6±33.0 seconds, P = .39). CONCLUSION: MK-801 glutamate hypofunction reduced hippocampal theta oscillations and impaired spatial working memory. MSN theta, but not gamma, stimulation improved spatial working memory following MK-801 administration.